Analysis of Tax Compliance Optimization in MSMEs: Case Study at KPP Pratama Kudus - Rosalina, Rita; Shodiq, Muhammad Ja'far; Shabihah, Khansa (Journal of Advanced Multidisciplinary Research, 2025)
In Indonesia, taxes are the primary source of state revenue and are a top priority in government management. The government gradually began to focus on Indonesia's Micro, Small, and Medium Enterprises (MSME) sector in 2013, which experienced accelerated growth due to the imposition of taxes on MSMEs. Nevertheless, taxpayer compliance in Indonesia remains an annual issue due to the low level of tax compliance. This investigation aims to investigate and analyze the impact of religiosity, love of money, and knowledge of taxation on taxpayers' compliance in MSMEs registered at KPP Pratama Kudus. Primary data was acquired through questionnaires in this investigation, which employs a quantitative methodology. The population of MSME taxpayers registered at KPP Pratama Kudus is the subject of this study, with a total sample of 178 respondents used. The technique employed in this investigation was random sampling. The SPSS version 25 software application is utilized to process the data analysis technique in this study, which involves multiple linear regression analysis. The findings of this investigation suggest that taxpayer compliance is significantly and positively influenced by religiosity, a fondness for money, and an understanding of taxation.